Revealing the correlation between charge carrier recombination and extraction in an organic solar cell under varying illumination intensity. Issue 38 (20th September 2017) - Sharma, Abhishek; Chauhan, Mihirsinh; Bharti, Vishal; Kumar, Manoj; Chand, Suresh; Tripathi, Brijesh; Tiwari, J. P.
Abstract : Herein, a theoretical model has been outlined in order to study the variation of different device parameters of an organic solar cell with various illumination levels. Abstract : The design and fabrication of better excitonic solar cells are the need of the hour for futuristic energy solutions. This designing needs a better understanding of the charge transport properties of excitonic solar cells. One of the popular methods of understanding the charge transport properties is the analysis of the J – V characteristics of a device through theoretical simulation at varied illumination intensity. Herein, a J – V characteristic of a polymer:fullerene based bulk heterojunction (BHJ) organic solar cells (OSCs) of structure ITO/PEDOT:PSS (∼40 nm)/PTB7:PC71 BM (∼100 nm)/Al (∼120 nm) is analyzed using one- and two-diode models at varied illumination intensity in the range of 0.1–2.33 Sun. It was found that the double diode model is better with respect to the single diode model and can explain the J – V characteristics of the OSCs correctly. Further, the recombination mechanism is investigated thoroughly and it was observed that fill factor (FF) is in the range of 62.5%–41.4% for the corresponding values of the recombination-to-extraction ratio ( θ ) varying from 0.001 to 0.023. These findings are attributed to the change in charge transport mechanism from trap-assisted to bimolecular recombination with the variation of illumination intensity.